State and Evolution of the Investigación y Educación en Enfermería Journal from a Metric Analysis (2021)
ABSTRACT: Objective. To analyze levels of production, reach, and thematic development of the Investigación y Educación en Enfermería journal from a scientometric analysis. Methods. The study collected 1,066 articles corresponding to the period between 1983 and 2020. The scientometric analysis was carried out from three components of descriptive analysis: performance of the publication, geographic reach, and thematic development. The first two used data consolidated from articles published in the Open Journal System at Universidad de Antioquia. The third component captured the bibliographic references from the Web of Science and Scopus databases and from the Google Scholar and Lens academic search engines. Results. In terms of the production analysis, the Journal shows stable behavior sustained over time with international reach regarding authorship. In the thematic setting, the Journal concentrates on two large clusters: 1) research on human factors from different perspectives and 2) cross-sectional studies differentiated mainly by sex. With respect to emerging clusters, on one side, a thematic pillar is seen with studies in young adult population and another in matters related to the educational process and nursing students. Conclusion. The Journal has maintained outstanding behavior in terms of production over time, aligned with very good visibility for potential authors internationally; something not easily accomplished for most journals in Colombia. Likewise, its production has had a thematic domain to a greater extent related to human factors associated with the nursing practice.